2015
DOI: 10.4103/1305-7456.163231
|View full text |Cite
|
Sign up to set email alerts
|

A different wax sculpture technique for implant-retained auricular prosthesis

Abstract: Replacement of missing ears is a challenging task in which extensive array of materials and techniques have been employed. This article describes a different and simplified procedure for fabricating auricular prostheses very similar to the intact left ear of the patient. A 65-year-old male patient was referred to the Department of Prosthodontics with the loss of the right ear. In this case, the impression was made using hydrocolloid material (alginate) from the both defected and the opposite side. After harden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…Brandao et al 4 also reported an auricular implant success rate of over 98%; two-implant retention showed the lowest failure rate. While adhesive-and bar-retained prostheses have shown clinical success, 7,23,24 a 2012 review by Sharma et al 25 identified benefits of implant retention versus adhesive. While approaches similar to the current situation (scanning, digitization and 3D-printing) have been reported, 9,10,12,13,26 all used conventional CT 9,10,13,26 or electron-beam tomography.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brandao et al 4 also reported an auricular implant success rate of over 98%; two-implant retention showed the lowest failure rate. While adhesive-and bar-retained prostheses have shown clinical success, 7,23,24 a 2012 review by Sharma et al 25 identified benefits of implant retention versus adhesive. While approaches similar to the current situation (scanning, digitization and 3D-printing) have been reported, 9,10,12,13,26 all used conventional CT 9,10,13,26 or electron-beam tomography.…”
Section: Discussionmentioning
confidence: 99%
“…Both acceptable 1,3,4,[6][7][8][9][10][11][12][13] and suboptimal outcomes have been reported. 6 Conventional analog approaches used to fabricate implant-retained auricular prostheses involve making a conventional impression of the affected and unaffected ear sites (using the intact ear as an indirect template), 7,14 fabrication of a gypsum-product master cast, 7,[15][16][17] and production of a wax pattern, 7,14,17 used to fabricate the definitive prosthesis via conventional flasking, wax-elimination, and molding and curing of the prosthesis, commonly using silicone. Various modifications of this conventional technique have been described with the objective of overcoming technique-sensitivity hurdles, such as tissue movement, 16 accurate reproduction of convoluted auricular anatomic dimensions with severe undercuts, 14 and impression distortion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O que determina a técnica a ser escolhida é a habilidade do profissional e a economia de tempo para a conclusão do caso. 10,11 Apesar de na literatura existirem várias técnicas para realizar o padrão de cera, a direta apresenta maior fidelidade das características da orelha do paciente. 12,13 Contrapondo a este fato, no presente caso, a técnica indireta foi a melhor opção disponível, uma vez que a escultura pelo método direto demandaria mais tempo para ser realizada, maior número de sessões clínicas, mantendo o paciente afastado das suas funções de trabalho por um período maior, bem como maior tempo de trabalho laboratorial.…”
Section: Discussão E Conclusõesunclassified
“…1,9,11 Assim, apesar das vantagens deste método, uma prótese auricular retida por adesivos, desde que manuseada adequadamente, proporciona também bons resultados e de uma forma não invasiva. 8,10 A retenção da prótese auricular por meio de armações de óculos é uma opção que, além de ser mais fácil fixação, favorece a higienização, uma vez que não apresenta o contato com substâncias químicas de forma frequente. 8 Apesar desta opção ter sido apresentada ao paciente, o mesmo ponderou o gasto na confeção de uma armação, uma vez que o mesmo não apresentava problemas visuais prévios, a falta de um apoio no tripé de suporte do óculos devido à falta do pavilhão auricular causando uma insegurança, além do fato de não poder utilizar a prótese sem o óculos, gerando um constrangimento caso necessitasse retirar o óculos em público e consequentemente ter que retirar a prótese, conforme questionamento em relação a banho de mar ou piscina.…”
Section: Discussão E Conclusõesunclassified